Splitsing: As a Method for Resolving Teddy Minahasa’s Narcotics Case in Criminal Justice Investigations - Romdoni, Muhamad; Abubakar, Aldestianah Putri; Nurtresna, Robby (LAW FACULTY UNISSULA, 2023)
Deliberate narcotics crimes typically involve multiple perpetrators or are coordinated to incorporate an element of participation. This is due to the fact that these crimes are carried out in groups and each individual is assigned specific responsibilities in order to accomplish predetermined objectives. In order to identify the principal perpetrators of group crimes, the public prosecutor is compelled to segregate the case files for the purpose of examination. As a result, this article aims to gain a deeper understanding of the splitting mechanism, which is utilized to divide the files of multiple perpetrators. This research employed a normative juridical approach, which is based on cases and legislation, and utilized secondary data in the form of legal materials. The complete dataset, consisting of primary, secondary, and tertiary legal materials, was subsequently gathered and subjected to deductive analysis. The results of this study indicate that case file splitting (splitting) is the division of a single file containing multiple perpetrators' information so that the public prosecutor may divide the file into multiple files based on the number of defendants. This is done in an effort to clear up the case and expedite the judge's evidentiary process. The provision pertaining to the division of case files is outlined in Criminal Procedure Code Article 142. Inspector General of Police Teddy Minahasa and his associates investigated a narcotics trafficking case using the splitting method, which involves the separation of case files. This approach has demonstrated significant efficacy in upholding the principles of fast, simple, and low-cost justice.